Q: What is the square root of 5ab the square root of 10ab squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

The GCF of 5ab and 56b squared is b.

(5ab)2 = 25a2b2 (provided a and b are elements of a commutative group).

No. 2a is one thing, 3b is another. If you add them together, they become 2a + 3b. 5ab indicates that multiplication has taken place. 5 times a times b = 5ab

Considering the minus sign between 5ab and 6b2 then we have the polynomial as 6a2 + 5ab - 6b2. The polynomial is a quadratic polynomial.Steps to factorize a quadratic polynomial:1 - Multiply first term by third term. 6a2 x (-6b2) = -36a2b22 - If possible break the second term into two terms such that they multiple to -36a2b2. If not then it is factorized by Sridharacharya's formula.5ab can be broken as 9ab + (-4ab).These two terms multiply to give -36a2b2.So we can write 6a2 + 5ab - 6b2 = 6a2 + 9ab + (-4ab) - 6b2.6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)(3a - 2b).So the factors are (2a + 3b) and (3a - 2b).

You add the coefficients, i.e., the numbers. For example, 3ab + 2ab = 5ab.

Related questions

What is The simplified form of (3a2 - 5ab plus c2) plus (-2a2 plus 10ab plus 6c2)

The GCF of 5ab and 56b squared is b.

35ab squared

35ab squared

(5ab)2 = 25a2b2 (provided a and b are elements of a commutative group).

(a - 2b)(2a - b)

55/5ab + 4/5ab = 59/5ab

7ab-5ab = 2

gcd of 5ab,28xy

-1ab^2 + 5b + 8 Step-by-step explanation: 3a^2+9ab+5-4a^2-4ab+3 3a^2-4ab^2=-1ab^2 9ab-4ab=5ab 5+3=8 -1ab^2+5ab+8

(5ab^2 + 4cd)(5ab^2 4cd) <

6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)